The effects of the repeated reading method from teachers’ perspectives of cycle one schools (1-4) - Al Saadi, Najla Hamed Hilal (International Journal of Educational Technology and Learning, 2023)
The ability to read during the early years of education plays a crucial role in students’ academic life. However, Cycle One Omani students continue to face significant challenges in reading fluently and comprehending texts. Many students struggle to read the assigned texts within a reasonable time, which negatively affects their ability to answer comprehension questions. This research paper focuses on grade three and four teachers’ opinion in North Al-Batinah Governorate regarding the repeated reading method, which they have been implementing in their classrooms for over six years. A designed and validated online questionnaire, to which 121 teachers responded was used to collect data. The study revealed that the majority of the participants strongly agreed on the effectiveness of the RR method in enhancing grade three and four students’ English language learning skills, particularly their reading fluency and overall English proficiency. Moreover, the data showed that RR is an effective, new and useful method, which made the teaching environment more interesting and broke the usual routine of teaching the reading skill. In addition, the results indicated that most grade three and four students enjoyed the RR experience and were motivated and eager when applying the RR method. Therefore, this study is one of the few in Oman to have investigated primary students’ reading skill, so it makes a distinguished contribution to the Omani context with regard to investigating young learners’ reading skills and strategies.